1965
DOI: 10.2337/diab.14.4.179
|View full text |Cite
|
Sign up to set email alerts
|

Sequential Changes in Adipose Tissue Metabolism in Alloxan-Diabetic Rats

Abstract: Alloxan-diabetic rats were maintained for two weeks on Protamine Zinc Insulin (4 U./day), and changes in adipose tissue metabolism were followed over a period of ninetysix hours after termination of insulin treatment. Blood glucose and plasma FFA showed parallel increases from sixteen to ninety-six hours after the last insulin injection. Blood ketones were elevated at seventy-two and ninety-six hours and lipid accumulation in the liver was also evident at these times. FFA release from isolated fat pads was ele… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

0
2
0
1

Year Published

1966
1966
1984
1984

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 18 publications
(3 citation statements)
references
References 0 publications
0
2
0
1
Order By: Relevance
“…The enzyme content of adipose tissue is high in the carbohydrate-fed state and low in the fasted or diabetic state. 18 -19 The possibility that lipoprotein lipase rather than alpha-glycerophosphate is initially more important, is suggested by recent in vitro studies of Tarrant and Ashmore, 20 who have indicated that four days after insulin withdrawal from diabetic animals there is impaired conversion of glucose to CO 2 and to fatty acid in epididymal fat pads while glycerophosphate production is unaffected. It would thus seem possible that fatty acid esterification may occur even at ninety-six hours after insulin withdrawal.…”
Section: Discussionmentioning
confidence: 94%
“…The enzyme content of adipose tissue is high in the carbohydrate-fed state and low in the fasted or diabetic state. 18 -19 The possibility that lipoprotein lipase rather than alpha-glycerophosphate is initially more important, is suggested by recent in vitro studies of Tarrant and Ashmore, 20 who have indicated that four days after insulin withdrawal from diabetic animals there is impaired conversion of glucose to CO 2 and to fatty acid in epididymal fat pads while glycerophosphate production is unaffected. It would thus seem possible that fatty acid esterification may occur even at ninety-six hours after insulin withdrawal.…”
Section: Discussionmentioning
confidence: 94%
“…It has been the general finding that adipose tissue of alloxan-diabetie animals (HAUS~]~GE~ et al [27], MZr,LSTEIN and HAUSBE~GE~ [38], W~EG~AD and SEAW [53] and WINEG~D and RE~OLD [54]; depancreatized rats (MmLIORINE and Cm~IKOFF [36] and FAIN et M. [14]; and antiinsulin-indueed diabetes (TA~AN~ and ASItMORE [48] and DIXIT et al [10]) have a decreased ability to oxidize glucose to C0~ or convert glucose to fatty acids and glycerol. Fat tissue from human diabetics has been reported to oxidize glucose to CO~ and synthesize fatty acids at a normM rate (BJO~To~ [2] and CAR~so~ and OSTMA~ [8]).…”
Section: Discussionmentioning
confidence: 99%
“…Beim manifesten Diabetes mellitus sind die nichtver esterten Fettsäuren im Nüchternserum erhöht (31,(39)(40)(41)(42)(43), ebenso bei der Adipositas, bei Hyperthyreosen und bei Leberzirrhosen (44)(45)(46)(47), wobei der Diabetes mellitus ein häufiges Symptom dieser Krankheitsbilder ist. Erhöhte Serumkonzentrationen der nichtveresterten Fettsäuren hemmen die Insulinwirkung auf die Muskulatur bzw.…”
Section: Diskussionunclassified